Terms anf Their Translation for Museum Labels - Gill, Marilyn (Meta, 1994)
AbstractWith the development in France of both general and specialized museums, and the growing cultural and touristic exchanges between countries, access to their information is becoming increasingly important. The aim of a long term research project of the English Linguistics Department of the University of Franche-Comté is to translate the French labels of a classified museum (the Museum of Fine Arts and Archeology of Besançon) into English and give practical training in terminology and translation to third year English for Special Purposes students. To do this, two different bilingual lexicons have to be created: one of the repetitive terms used by the Museum to describe the exhibits, i.e. museological terms, and the other of the subject of the label, i.e. in 1993 Egyptology. The theoretical problems and practical solutions concerning the compilation of highly specific bilingual lexicons, the translation of maximum information telegraphic style texts and the choice of specialized terms to be used for a general museum public of all ages as well as the teaching outcomes of such a project are discussed.